A STUDY ON THE EFFECTIVENESS OF USING ALPHABET CARDS GAME IN TEACHING VOCABULARY FOR COMMERCIAL BUSINESS ADMINISTRATION STUDENTS - Arita Destianingsih; Ari Satria (Universitas Ahmad Dahlan)
The aim of this study was to know the effectiveness of the use of alphabet cards game as interesting tool to explain vocabularies and it make it easier to remember their meanings. This study belongs to the quasi experimental research and presents pre-test, post test and to investigate the effect of using alphabet cards game on vocabulary mastery of commercial business administration students. The participants were the students from commercial business administration students at the third semester (N=54) of State Polytechnic Bengkalis and divided into two groups. Both groups were taught vocabulary, however, the experimental group students who are exposed to alphabet cards game and the controlled group students who received conventional method. Pre-test and post-test were given to both experimental group students and controlled group students. The score of the vocabulary tests were compared through independent sample t-test. The mean value of pre-test of experimental class was 61.35, while the control class was 52.23. After learning using alphabet card games in experimental class the mean value obtained in post-test was 78.85, while in control class was 59.04. The improved of learning outcomes can be seen from the level of significance was 0.000 and it was lower than t test 0.000<0.05. It means that the hypothesis null is not accepted. Therefore, it can be concluded that the score of the students in learning vocabulary between the experimental group and control group was significantly different. The experimental group students who learned vocabulary using alphabet cards game had increased their vocabulary mastery.